2014
DOI: 10.1002/adma.201403039
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Assembly of Single Nanowires through Capillary‐Assisted Dielectrophoresis

Abstract: An innovative technique is proposed for the precise and scalable placement of 1D nanostructures in an affordable manner. This approach combines the dielectrophoresis phenomenon and capillary assembly to successfully align thousands of single nanowires at specific locations at the wafer. The nanowires are selectively trapped by taking advantage of the material--specific frequence dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
83
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 28 publications
2
83
0
Order By: Relevance
“…Capillary force ( F c ) and alternating‐electric field (AEF) have been reported to be effective for the assembly of postgrowth nanocrystals . Cui et al reported the hierarchical assembly of isotropic and anisotropic colloidal nanostructures over large areas by capillary force.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Capillary force ( F c ) and alternating‐electric field (AEF) have been reported to be effective for the assembly of postgrowth nanocrystals . Cui et al reported the hierarchical assembly of isotropic and anisotropic colloidal nanostructures over large areas by capillary force.…”
mentioning
confidence: 99%
“…For instance, Freer et al adopted F DEP to manipulate and address silicon nanowires in large area . Collet et al combined F DEP and F c to pattern silicon nanowires . Besides the silicon nanowires, recently the electric field was utilized to achieve in situ growth and patterning of organic single crystals on electrode patterns .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…39 And even more resource efficient parallel and unsupervised assembly processes can be also potentially adopted for this. [26][27][28][29] Hence, the assembly process may be further streamlined substantially lowering the associated costs.…”
Section: Discussionmentioning
confidence: 99%
“…So far such integration has been demonstrated only for micrometer-scale components, 12,[19][20][21][22][23][24][25] and it has been shown that heterogeneous integration can be done in a very efficient way by parallel and unsupervised self-assembly. [26][27][28][29] Micro-and nanoscale components are typically fabricated on rather thick (down to 25 lm, typically 200-300 lm thick) and large (down to 25 lm, typically 5-15 mm lateral dimensions) dies due to practical limitations regarding die a) Present address: International Iberian Nanotechnology Laboratory, Av.…”
Section: Introductionmentioning
confidence: 99%